ANALISIS PERTIMBANGAN HUKUM HAKIM DALAM PUTUSAN NOMOR 23/Pdt.Sus-PHI/2020/PN.Bjm TENTANG GANTI RUGI TERHADAP KECELAKAAN KERJA - NIM. A1011201229, PUTRI ANGRAINI (Fakultas Hukum Universitas Tanjungpura, 2024)
Abstract The company as the employer is responsible for workplace accidents or the company to address the loss of income due to the risk of death or disability. Workers' accident insurance for victims of workplace accidents is crucial because it is at that moment that workers need assistance that they may not be able to afford. Workers who experience workplace accidents can demand accountability from the company where they work. However, if the company neglects this responsibility, workers can file a lawsuit in the Industrial Relations Court at the District Court. This was seen in Decision Number 23/Pdt.Sus-PHI/2020/PN.Bjm filed with the Industrial Relations Court at the Banjarmasin District Court. Regarding Rina Ariana, S.H. as the Plaintiff filed a lawsuit against PT. Habco Primatama as the Defendant to pay Death Compensation and other rights.The problem statement of this research is